2004
DOI: 10.1111/j.1365-2222.2004.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Phleum pratense pollen starch granules induce humoral and cell‐mediated immune responses in a rat model of allergy

Abstract: It was confirmed that timothy grass pollen contains allergen-loaded SG, which are released upon contact with water. These granules were shown to be recognized by pollen-sensitized rats sera and to trigger lymph node cell proliferation in these rats. These data provide new arguments supporting the implication of grass pollen SG in allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Allergen-bearing starch granules obtained upon contact of pollen with water have been shown to create an inhalable allergenic aerosol capable of triggering an early asthmatic response in an experimental in vitro study. Starch granules were shown to be recognised by pollen sensitised in rat serum and to trigger lymph node cell proliferation in these rats [29]. These data provide new arguments supporting the implication of grass pollen starch granules in thunderstormrelated asthma.…”
Section: Possible Mechanisms For Thunderstorm-related Asthmasupporting
confidence: 49%
“…Allergen-bearing starch granules obtained upon contact of pollen with water have been shown to create an inhalable allergenic aerosol capable of triggering an early asthmatic response in an experimental in vitro study. Starch granules were shown to be recognised by pollen sensitised in rat serum and to trigger lymph node cell proliferation in these rats [29]. These data provide new arguments supporting the implication of grass pollen starch granules in thunderstormrelated asthma.…”
Section: Possible Mechanisms For Thunderstorm-related Asthmasupporting
confidence: 49%
“…This suggests that lower concentrations of ozone might also induce significantly higher PCG release. PCG have been shown to contain allergens [10] and to be able to trigger an IgE-mediated response in rats [11] and asthmatic patients [16]. In previous studies, pollen-specific IgE ELISA inhibition experiments showed that 2.6 × 10 6 PCG contained as much allergen as in 100 µg of pollen.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, pollen-specific IgE ELISA inhibition experiments showed that 2.6 × 10 6 PCG contained as much allergen as in 100 µg of pollen. Knowing this, we then observed that for the same amount of allergens, PCG triggered a higher in vitro cellular response than intact pollen or pollen extract [10], indicating that PCG increased the bioavailability of pollen allergens. This may be explained by their particulate nature [17] and/or due to the more efficient presentation by antigen-presenting cells [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These granules, which contain most of the pollen major allergens, have been implicated in thunderstorm-associated asthma [21, 22]. They have also been shown to trigger primary and secondary allergic responses in pollen-sensitised Brown Norway rats [23, 24]. Recently, Zinnia pollen exposed to polluted air has been shown to trigger higher allergic responses in guinea pig [18].…”
Section: Introductionmentioning
confidence: 99%